Comparison of RNA localization during oogenesis within Acipenser ruthenus and Xenopus laevis - Iegorova, Viktoriia; Naraine, Ravindra; Psenicka, Martin; Zelazowska, Monika; Sindelka, Radek (Frontiers in Cell and Developmental Biology, 2022)
The oocyte is a unique cell, from which develops a complex organism comprising of germ layers, tissues, and organs. In some vertebrate species it is known that the asymmetrical localization of biomolecules within the oocyte is what drives the spatial differentiation of the daughter cells required for embryogenesis. This asymmetry is first established to produce an animal-vegetal (A-V) axis which reflects the future specification of the ectoderm, mesoderm, and endoderm layers. Several pathways for localization of vegetal maternal transcripts have already been described using a few animal models. However, there is limited information about transcripts that are localized to the animal pole, even though there is accumulating evidence indicating its active establishment. Here, we performed comparative TOMO-Seq analysis on two holoblastic cleavage models: Xenopus laevis and Acipenser ruthenus oocytes during oogenesis. We found that there were many transcripts that have a temporal preference for the establishment of localization. In both models, we observed vegetal transcript gradients that were established during either the early or late oogenesis stages and transcripts that started their localization during the early stages but became more pronounced during the later stages. We found that some animal gradients were already established during the early stages, however the majority were formed during the later stages of oogenesis. Some of these temporally localized transcripts were conserved between the models, while others were species specific. Additionally, temporal de novo transcription and also degradation of transcripts within the oocyte were observed, pointing to an active remodeling of the maternal RNA pool.